The Spatial Network Contagion of Environmental Risks Among Countries Along the Belt and Road Initiative - Lu, Ling; Fang, Kai; Liu, Chuan Ming; Sun, Cheng (Frontiers in Environmental Science, 2021)
Under the tide of global economic integration, the risks of environmental pollution have become intensified. The close exchange of activities among the countries under the Belt and Road Initiative (BRI)will especially feel this contagion of environmental risks. Given this situation, this paper analyses the environmental risk contagion relations among the BRI countries and the characteristics of their network structure by using social network analysis (SNA). A block model was used to analyze the spatial clustering characteristics of the spatial correlation infectivity of environmental risks. Specifically, the influencing factors of spatial network contagion of environmental risk in the BRI were analyzed through the Quality Assurance Procedure (QAP) of SNA. The results of this paper provide a reference for the BRI to reduce the environmental risks and jointly control environmental risk contagion, so as to assist in the promotion of a green BRI.